Mapping peatland distribution and quantifying peatland below‐ground carbon stocks in Colombia's Eastern Lowlands - Uhde, A.; Hoyt, A. M.; Hess, L.; Schmullius, C.; Mendoza, E.; Benavides, J. C.; Trumbore, S.; Martin-Lopez, Javier Mauricio; Skillings‐Neira, P. N.; Winton, R. S. (Wiley, 2025)
The extent and distribution of tropical peatlands, and their importance as a vulnerable carbon (C) store, remain poorly quantified. Although large peatland complexes in Peru, the Congo basin, and Southeast Asia have been mapped in detail, information on many other tropical areas is uncertain. In the Eastern Colombian lowlands, peatland area estimates range from 700 km 2 to nearly 60,000 km 2, leading to highly uncertain C stocks. Using new field data, high‐resolution Earth observation (EO), and a random forest approach, we mapped peatlands across Colombian territory East of the Andes below 400 m elevation. We estimated peatland extent using two approaches: a conservative method focused on medium‐to‐high peat probability areas and a more inclusive one accounting for large low‐probability areas. Multiplying these extents by below‐ground carbon density yields a conservative estimate of 0.95 (0.6–1.39 Pg C, 95% confidence interval) over 9,391 km 2 (7,369–11,549 km 2 ) and up to 2.86 Pg C (1.76–4.22 Pg C) across 29,069 km 2 (22,429–36,238 km 2 ). Among four potentially peat‐forming ecosystems identified, palm swamps and floodplain forests contributed most to the peat extent and C stock. We found that most peatland patches were relatively small, covering less than 100 ha. We compared our map to previously published global and pan‐tropical peat maps and found low spatial overlap among them, suggesting that peat maps uninformed by local field information may not precisely specify which landscape areas within a peatland‐rich region are actually peatlands. We further assessed the suitability of different EO and climate variables, highlighting the need for high‐resolution data to capture local heterogeneities in the landscape.